The opposition between light and darkness in the argumentation of the so-colled philosophia prima: selected problems pertaining to metaphysics - Rembierz, Marek (Folia Philosophica, 2003)
The ways of argumentation analysed in the present article are meant to satisfy the postulate of investigating into what is first; they are based on the assumption that it is possible to arrive at what is first, and, while describing what is first, they refer to the opposition of light vs. darkness. Such ways of argumentation can be found, inter alia, in the works of the Pre-Socratics, in the Platonic metaphor of the cave, in Aristotle’s texts, where he develops a theory of arriving at what is the first, in Plotinus’s vision in, and in many later conceptions referring in one way or another to the above mentioned Greek sources. Additionally, the author takes into consideration various problems arising from modem changes in philosophy and connected with the traditional questions about the function of the opposition between light and darkness and related ideas from the circle of metaphysics and theory of cognition. Paramount, in the argumentation of the first philosophers, is the relationship between pairs of opposite ideas such as light vs. darkness, or finite vs. infinite. The said relationship is one of the sources of the categories used in metaphysic and in theory of cognition. The Greeks put forward a model of the world in which light is partly responsible for the visible order; they made light penetrate the realm of cognition. Many fundamental philosophical terms (such as “the light of reason,” “idea,” “theory,” “intuition,” “clarity,” “obviousness”) are permeated with metaphors originating from the opposition between light and darkness. The terms in question are derived from figures involving the action of light, the relationship between murkiness and luminosity, the function, the function of eyesight and optical effects. The role of the discussed opposition is particularly remarkable in the current of thought known as “the metaphysics of light.” Changes in light metaphors are strictly connected with changes in ontological models. This correlation can be traced back to Greek models. The opposition between light and darkness has always been interpreted within a specific metaphysical framework.